2011
DOI: 10.1159/000322997
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Anaphylaxis in Hospitalized Patients

Abstract: Background: Only two studies have analyzed the incidence of anaphylaxis during admission to hospital. We have analyzed the incidence of anaphylaxis among hospitalized patients and determined the timing of and risk factors for episodes of anaphylaxis. Methods: Our study was performed between 1999 and 2005. We used the definition of anaphylaxis of the NIAID-FAAN symposium. Cases of anaphylaxis were extracted from an official database of discharge diagnoses coded according to the International Classification of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
1
14
2
Order By: Relevance
“…Our findings reveal a higher percentage of visits to the ED due to anaphylaxis than previously reported in other adult ED studies [6,8,19,20], although they are comparable to our pediatric ED estimate [21] (table 4). Differences in populations and ED referral patterns may contribute to the higher rate of anaphylaxis in our adult ED center.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings reveal a higher percentage of visits to the ED due to anaphylaxis than previously reported in other adult ED studies [6,8,19,20], although they are comparable to our pediatric ED estimate [21] (table 4). Differences in populations and ED referral patterns may contribute to the higher rate of anaphylaxis in our adult ED center.…”
Section: Discussionsupporting
confidence: 89%
“…However, the incidence of anaphylaxis in our emergency department was 57.84 episodes per 100 000 person‐years, almost 15 times than that reported by Harduar–Morano et al. Likewise, the use of codes proposed by these authors did not reveal any additional patients in a cohort of 114 749 discharges of our hospital, which was the source for retrieval in a series of hospitalized patients with anaphylaxis recently published by our group . Consequently, this comparison confirms the effectiveness of our retrieval method.…”
Section: Discussionmentioning
confidence: 78%
“…The risk of anaphylaxis in hospital was analysed by Tejedor‐Alonso et al. and in the International Collaborative Study of Severe Anaphylaxis . The results showed that many standard NSAIDs and ß‐lactam antibiotics carried a lower risk of triggering anaphylaxis than other drugs (number of episodes of anaphylaxis divided by the number of persons taking the drug or by the number of doses received) (Table ).…”
Section: How Frequent Is Anaphylaxis?mentioning
confidence: 99%